2001
DOI: 10.1002/1521-4141(200103)31:3<802::aid-immu802>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Thymic export in aged sheep: a continuous role for the thymus throughout pre- and postnatal life

Abstract: A diverse repertoire among peripheral T cells is established in early life by thymic export when the naive T cell pool is first formed. In contrast, during adult life the thymus has been thought to play only a minor role in T cell homeostasis. As individuals age there is an increasing proportion of peripheral T cells bearing a memory phenotype, as well as a corresponding decrease in the number of naive T cells. The change in the composition of the peripheral T cell pool with age is thought to occur as a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…According to Kratochvil et al (1996) thymus growth was more than double in thymus of male kids between 24 to 42 days of age. Cunningham et al (2001) observed 42 gram of mean thymus weight at 2 weeks old lambs, while significant amount of thymus tissue (18 gram) was present even at the age of 3 to 4 years in sheep. Ramayya et al (2008) recorded maximum weight (166 gram) of thymus in postnatal buffalo calves at 3 months of age and thereafter the mean weight of the thymus decreased gradually.…”
Section: Biometrical Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…According to Kratochvil et al (1996) thymus growth was more than double in thymus of male kids between 24 to 42 days of age. Cunningham et al (2001) observed 42 gram of mean thymus weight at 2 weeks old lambs, while significant amount of thymus tissue (18 gram) was present even at the age of 3 to 4 years in sheep. Ramayya et al (2008) recorded maximum weight (166 gram) of thymus in postnatal buffalo calves at 3 months of age and thereafter the mean weight of the thymus decreased gradually.…”
Section: Biometrical Studiessupporting
confidence: 82%
“…Radmehr et al (1997) also reported that the ratio of thymus to body weight decreases with advancement of age in sheep from 5 months to 8 years of age. Furthermore, Cunningham et al (2001) observed that the weight of thymus as a percentage of body weight was 0.5% in neonatal lambs, which was much greater than in adult sheep (0.05 % body weight). These observations were in line with present work.…”
Section: Biometrical Studiesmentioning
confidence: 99%
“…In mice and humans no definite cell surface phenotype has been determined to identify RTE, although in the rat CD4 ϩ RTE are described as CD45RC Ϫ CD90 ϩ (21). Intrathymic FITC labeling has been widely used to identify CD4 RTE in mice and other experimental animals and to establish that their Ag responsiveness and cell surface phenotype is comparable to that of unlabeled CD4 cells (22)(23)(24), but this technique has not previously been used in the context of research in aging. Two studies were recently published that examine RTE in young (25) and aged (26) mice transgenic for GFP under control of the RAG-2 promoter.…”
Section: Environmental and Intrinsic Factors Lead To Antigen Unresponmentioning
confidence: 99%
“…A cannula was inserted into the jugular vein for administering BrdU and collecting blood samples. To determine thymic export rates, an aqueous solution of CFSE (100 lM; Molecular Probes) was injected directly into the cervical thymus at multiple sites as described previously [46]. Animals were killed with an i.v.…”
Section: Animals and Surgerymentioning
confidence: 99%